"I might not fit that doctor image": Ideal worker norms and women medical students. Issue 3 (15th December 2021) - Blalock, A. Emiko; Smith, Margaret Chandler; Patterson, B. R.; Greenberg, Amy; Smith, Brandon R. G.; Choi, Christine
Abstract: Despite the increasing numbers of women students in medical schools, focused attention on their perceptions about medical school and the medical profession remain underexamined. These perceptions are important to understand, particularly since women students are likely burdened with a host of gender norms related to work, family, and their future roles as physicians. Early experiences in medical school offer important insights into the larger student experience and are tied to academic outcomes and feelings of belonging. To examine early experiences of women medical students, this qualitative study used sensemaking theory to describe the current context and "story" of ideal worker norms. Critical qualitative interviews of 38 women students were performed during their first 2 months of medical school and explored both how the students perceived and experienced ideal worker norms, and how they made sense of the "story" of ideal worker norms. The participants described ways they encountered gendering and ideal worker norms through displays of nurturing behaviour, expectations to balance a future family, and whether they looked or acted the part of a doctor. This article highlights the challenges women medical students are already aware they will face, the opportunities they look forward to, and the strengths they anticipate leaning on to navigate their profession. Results from this study have implications for women medical students' learning experiences and transitions into medical school and for faculty, staff, and scholars concerned with challenging gendering norms that shape medical education. Abstract : Women students are seen to demonstrate knowledge of "ideal worker norms" very early in medical school; the authors explore how they made sense of norms and began to navigate the gendered organization of their chosen careers.